Liquid-liquid extraction of lipase produced by psychrotrophic yeast Leucosporidium scottii L117 using aqueous two-phase systems - Duarte, Alysson Wagner Fernandes; Lopes, André Moreni; Molino, João Vitor Dutra; Pessoa, Adalberto; Sette, Lara Durães [UNESP] (Elsevier, 2015)
Aqueous two-phase systems (ATPS) have been used in biomolecules separation and as an efficient alternative to traditional purification systems for lipases extraction. Here, we investigated the partitioning and recovery of lipase derived from Leucosporidium scottii L117 using ATPS and aqueous two-phase micellar systems (ATPMS). Thus, we evaluated three ATPS: (i) polyethylene glycol (PEG)/phosphate salts and (ii) PEG/polyacrylic acid (NaPA) in different molecular weights (1500, 4000 and 8000 g/mol). (iii) Triton X-114 (TX-114)/McIlvaine buffer pH 7.0 in different conditions (2.0% (w/w) of TX-114 at 25.0 and 28.0 °C). The PEG/phosphate and PEG/NaPA systems resulted in a great loss of enzymatic activity; thus these systems do not represent viable alternatives for these lipase extraction. The micellar systems yielded the best results for lipase extraction with enzyme activity balances ranging between 84.7% and 113.05%. After optimizing the micellar system by experimental design of the partition coefficient of lipase increased by 10.3-fold (0.75-7.76). Lipase preferentially partitioned into the micelle-rich phase with KLip = 7.76, %RECBot = 93.85% and PF = 1.2 at 25.03 °C, 5.1 pH and 10.38% TX-114 and KLip = 4.77, %RECBot = 73.53% and PF = 1.97 at 28.00 °C, 4.5 pH and 8.0% TX-114, indicating that the ATPMS represents an alternative to purification/extraction of lipase L. scottii L117. A crude lipase extract was also evaluated to define the optimum pH and temperature. Lipase reached optimal activity at 40 °C, and remained stable in pH values ranging from pH 3.0 to 8.0 and temperatures from 20.0 to 45.0 °C, with relative residual lipase activity above 80% after 30 min of incubation.
Keywords: Aqueous two-phase systems; Downstream processing; Lipase activity; Polyethylene glycol; Triton X-114